The Image of Historical Memory Created by Writers: The Battle of Saulė in Latvian Literature - Butkus, Vigmantas (Colloquia, 2024)
Using memoir studies and literary imagology as the methodological starting points, the article analyses the image of the Battle of Saulė that took place on 22 September 1236 in the works of fiction and poetry by Latvian writers and the place of Lithuanians in it. Texts written in the 1910s–1930s, many of which were inspired by the 700th anniversary of the battle celebrated in 1936, are covered in the analysis. These are verses, poems, novels, and other literary genres written by Vilis Plūdons (real name Vilis Lejnieks, 1874–1940), Kārlis Fimbers (1898–1970), Rihards Ērglis (1881–1950), Jānis Akuraters (1876–1937), Atis Ķeniņš (1874–1961) and other authors. Latvian writers aimed: 1) to give prominence to the role of their countrymen (Semigallians), which is inadequate to objective historical data, 2) to express the idea of affinity and unity of the Balts through the topic of the battle. The first purpose was emphasised more strongly. The image of Lithuanians in the works under analysis is quite featureless, artistically expressionless; moreover, it is historically inaccurate (for instance, the legendary duke Ringaudas has been systematically depicted as a historical personality).